3D mapping with depth sensing cameras - Jek, Howard Kai Zhi (Nanyang Technological University, 2023)
The pursuit of perfection in Three-dimensional (3D) models has always been at the forefront of the field of computer graphics. The technique of producing 3D representations of real-world objects or surfaces has become widespread in recent years for a multitude of industries, adopting its use to better help its users perform visualization and run simulations with higher accuracies. Traditionally, 3D models are created manually on 3D software (such as AutoCAD) that required a substantial amount of work and precision to replicate its real-world counterparts. However, with the development and commercialisation of 3D cameras, the work is simplified and streamlined into an autonomous process allowing anyone to produce and utilise a 3D model. This project aims to demonstrate the process of generating 3D models using a Red, Green, Blue, and Depth (RGB-D) Camera with the aid of publicly available libraries like OpenCV, MediaPipe, and Open3D.